Convergence towards digitised content - Turner, Nicholas Frederick (My University, 2011)
Publishers today find themselves in an industry that may be on the verge of rapidly evolving towards new potentially disruptive forms of multimedia content brought about by convergence (contextually defined as the coming together of print, electronic media, computer content and book publishing as a result of emerging technologies). Strategic decisions need to be made on the extent to which publishers venture into new markets, taking into account how the South African specific context creates obstacles, or even opportunities. This research investigates the various factors influencing educational publishers in making these choices, based on literature findings of global trends, and in-depth qualitative interviews with executive directors of large local educational publishing houses. The main findings of the research were that South African educational publishers are generally adopting a reactive strategic stance to the offering of ‘converged’ content. These strategies commonly include reacting when local competitors advance, learning from better resourced developed country counterparts, and tentatively investing in digital supplements to conventional text in user-friendly ‘blended learning’ forms. Their subjective strategic choices are resulting from the consideration of a number of explored factors such as: the lack of resources due to the digital divide; governmental spending post revised curriculum implementation; the question of agility versus size; copyright issues surrounding digital rights management; the disintermediating threat or potential alliance offered by search engines such as Google; and the degree of proactivity chosen in early attempts at grabbing market share. The study was particularly relevant to the South African educational publishing market due to the scarcity of local research in the area of study, and the need for a snapshot of current trends at a potentially revolutionary time for both the scope of publishing and the future of printed content
MBA - WBS
Keywords: Digitised content; Publishers